Groundwater modelling with limited data sets: the Chari–Logone area (Lake Chad Basin, Chad). Issue 11 (25th June 2013) - Candela, L.; Elorza, F. J.; Tamoh, K.; Jiménez‐Martínez, J.; Aureli, A.
Abstract One of the most important issues for water resource management is developing strategies for groundwater modelling that are adaptable to data scarcity. These strategies are particularly important in arid and semi‐arid areas where access to data is poor and data collection is difficult, such as the Lake Chad Basin in Africa. In the present study, we establish a numerical groundwater flow model and evaluate the effects of dry and wet periods on groundwater recharge in the Chari–Logone area (96 000 km2) of the Lake Chad Basin. Boundary conditions, flow direction, sources, and sinks for the Chari–Logone local model were obtained by revising and remodelling the Lake Chad Basin regional hydrogeological model (508 400 km2) developed by the BRGM (Bureau de Recherches Géologiques et Minières) in the 1990s. The simulated aquifer water level showed good agreement with observed levels. Aquifer recharge is primarily determined by river–aquifer interactions and mostly occurs in the southern section of the study area. In wet years, groundwater recharge also occurs in the N'Djamena area. The approach we adopted provided relevant results and was useful as an initial step in more detailed modelling of the area. It also proved to be a useful method for groundwater modelling in large semi‐arid and arid regions where available data are scarce. Copyright © 2013 John Wiley & Sons, Ltd.